Pemetaan Daerah Bencana Letusan Gunung Api Salak Di Kecamatan Pamijahan Kabupaten Bogor Dan Rencana Jalur Evakuasi Berbasis Sistem Informasi Geografis - Firman Adityo; Angela Glorya Marito Samosir; Kusuma Kusuma; Sugeng Tri Utomo (Geosfera: Jurnal Penelitian Geografi, 2025)
Indonesia, as a country with intense tectonic and volcanic activity, faces a high risk of volcanic eruptions, including Mount Salak in Bogor Regency, West Java. This study aims to identify the eruption risk level of Mount Salak based on Geographic Information System (GIS) and determine evacuation routes in Pamijahan District. The study uses a quantitative method with secondary data processed through QGIS application. The data includes topography, population, infrastructure, and administrative boundaries to map risks and plan mitigation measures. The results indicate that Pamijahan District has a high risk, particularly in the villages of Ciasihan and Gunungsari, which are the most affected areas. The evacuation routes were designed using GIS to ensure efficient accessibility and the safety of the community. The affected infrastructure includes 49 km of roads, 15 hectares of buildings, and 21,049 m² of residential areas. The estimated number of people affected is around 950.